Analisis Faktor-Faktor yang BerpengaruhTerhadap Penerimaan Aplikasi Stikom Institutional Repository (SIR) dengan Metode UTAUT pada Institut Bisnis dan Informatika Stikom Surabaya - Annisa, Cyntia Al; Sulistiowati, Sulistiowati; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Library of the Institute of Business and Information Stikom Surabaya already use digital library system to improve the standard repository system to create an application that is named sir.stikom.edu. Ranked by webometric the repository fields, SIR is ranked 32 in Indonesia. The libraries want that SIR Stikom Surabaya entered the top 10 in webometric so as to improve the image of Stikom Surabaya. But now the library does not have a benchmark to evaluate the level of reception SIR to improve the ranking webometric. Based on these issues, libraries need a benchmark to determine the extent to which the level of acceptance of the implementation of applications that have been done. This research can determine what factors that influence the acceptance of information technology among students Stikom Surabaya using UTAUT models. Based on the survey results revealed several factors for the receipt of applications SIR based models UTAUT ie, Behavioral Intention has a strong influence on the Use Behavior. Moderating variable has not been proven to have a strong influence on the relationship between the dependent variable and independent variables.